2023
DOI: 10.3389/fphar.2023.1124693
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection dysregulates the expression of clinically relevant drug metabolizing enzymes in Vero E6 cells and membrane transporters in human lung tissues

Abstract: SARS-CoV-2-mediated interactions with drug metabolizing enzymes and membrane transporters (DMETs) in different tissues, especially lung, the main affected organ may limit the clinical efficacy and safety profile of promising COVID-19 drugs. Herein, we investigated whether SARS-CoV-2 infection could dysregulate the expression of 25 clinically relevant DMETs in Vero E6 cells and postmortem lung tissues from COVID-19 patients. Also, we assessed the role of 2 inflammatory and 4 regulatory proteins in modulating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…On the samples obtained in 2017-2018, we investigated the expression of the most clinically relevant ABC drug transporter genes, such as ABCB1 (P-gp), ABCC1 (MRP1), and ABCG2 (BCRP), expressed in the lungs [50]. Our findings revealed higher expression of the ABCB1 gene in patients with active inflammation activity.…”
Section: Discussionmentioning
confidence: 95%
“…On the samples obtained in 2017-2018, we investigated the expression of the most clinically relevant ABC drug transporter genes, such as ABCB1 (P-gp), ABCC1 (MRP1), and ABCG2 (BCRP), expressed in the lungs [50]. Our findings revealed higher expression of the ABCB1 gene in patients with active inflammation activity.…”
Section: Discussionmentioning
confidence: 95%
“…However, the data presented herein demonstrated that the potency and toxicities of some drugs, especially NA inhibitors were cell-system dependent. This was not unexpected since different cell types may have unequal distributions of drug metabolizing enzymes and membrane transporters [ 201 ], and certain antiviral agents (e.g., remdesivir and nirmatrelvir) are substrates of the Cytochrome P450 enzymes, P-glycoprotein, and other cell membrane transporters [ 202 , 203 ]. Also, NA phosphorylation may be cell-dependent [ 138 , 139 ].…”
Section: Discussionmentioning
confidence: 99%